Outcomes of primary percutaneous coronary interventions in nonagenarians with acute myocardial infarction. (1st August 2015) - Helft, Gérard; Georges, Jean-Louis; Mouranche, Xavier; Loyeau, Aurélie; Spaulding, Christian; Caussin, Christophe; Benamer, Hakim; Garot, Philippe; Livarek, Bernard; Teiger, Emmanuel; Varenne, Olivier; Monségu, Jacques; et al.
Abstract: Background: Few data are available on primary percutaneous coronary intervention (pPCI) in nonagenarians. In a large prospective registry on pPCI for STEMI we compared the demographics, procedural and in-hospital outcomes between nonagenarians (age ≥  90 years) and patients aged < 90 years. Methods and results: We included 26, 157 consecutive patients with pPCI in the Greater Paris Area region between 2003 and 2011. Of these, 418 (1.6%) were ≥ 90 years old. Nonagenarians (versus patients < 90 years) were more likely to be female (62.3% versus 22.5%, p < 0.0001), nonsmokers (81.6% versus 36.7%, p < 0.0001), in cardiogenic shock (Killip IV) upon admission (10.5% versus 4.8%, p < 0.001), and had significant co-morbidities. Over two-thirds of patients underwent procedures via the radial artery (61% versus 72.1%, p = 0.007). Both groups had high and similar angiographic success rates (98.1% versus 98.7%, p = 0.33). Drug-eluting stents were used less often in nonagenarians (4.4% versus 16.7%, p < 0.0001). Hospital mortality was significantly much higher in patients over 90 years old (24.9% versus 5.1%, p < 0.001) in univariate analysis. After adjustment for sex, cardiogenic shock, diabetes, triple vessel disease, drug-eluting stent use and glycoprotein IIb/IIIa inhibitors use, mortality remains higher in nonagenarian patients (OR: 4.31; 95% CI: 3.26–5.71, p < 0.0001). Conclusions: In a real-world setting, we found important demographic differences in nonagenarian compared to younger patients. Despite achieving a high rate of reperfusion with pPCI using mainly radial access, similar to that achieved in younger patients, hospital mortality was higher in nonagenarians. Highlights: Few data exist on nonagenarians who benefit from primary angioplasty. Primary percutaneous coronary intervention is feasible in nonagenarian patients. Hospital mortality was five times greater than that of younger patients.